Effect of PGPR on Scierotinia scierotiorum infection through elicitation of Phenylalanine Ammonia Lyase in Chickpea - S.C. CHATTERJEE, S. AMEER BASHA* and (Indian Phytopathology, 2007)
Foliar spray and micro-injection of plant growth-promoting rhizobacterial (PGPR) strains, viz., Pseudomonas fluorescens (Pf4) and P. aeruginosa (Pag), on chickpea (Cicer arietinum l.) induced synthesis of phenylalanine ammonia lyase (PAL) when challenged against Sclerotinia sclerotiorum. In both the treatments increased PAL activity was observed compared to the untreated control. However, higher PAL activity in foliar spray compared to micro-injection was observed. Thus the present investigation suggests that foliar spray with PGPRstrains is an effective method and could be used to manage diseases under field conditions. Further, maximum PAL activity observed after 48 h in both the methods as well as by both the Pseudomonas strains is suggestive of induced systemic resistance (ISR). Between the two strains, P. fluorescens was found to be relatively superior to P. aeruginosa in inducing PAL activity whereas the effect on PAL induction was more persistent with Pag.